A multi‐phase study for the development of a self‐efficacy measuring scale for ostomy care nursing management. (3rd November 2019) - Dellafiore, Federica; Pittella, Francesco; Arrigoni, Cristina; Baroni, Irene; Conte, Gianluca; Di Pasquale, Cristina; Casole, Lorenzo; Villa, Giulia; Caruso, Rosario
Abstract: Aim: To develop and psychometrically test a self‐efficacy scale for ostomy care nursing management. Design: This study adopted a multi‐method and multi‐phase design. Method: Phase 1 of the study was comprised of the developmental tasks, where items were generated based on the emergent themes from literature. The items were then discussed with a panel of experts. Phase 2 focused on the validation process of the scale, where its content validity, construct and concurrent validity, and its internal consistency were assessed. The validation process was conducted between January 2018 ‐ January 2019. Results: The final version of the self‐efficacy scale in ostomy care nursing management encompasses 24 items in three domains, namely the clinical assessment domain, the education and relationship domain, and the teamwork domain. The scale showed the evidence of face and content validity, adequate construct and concurrent validity, and adequate internal consistency. Conclusion: The developed scale can be used in clinical and educational research. Impact: This study presents the development and validation of the first valid and reliable self‐reporting measurement for nurses' self‐efficacy in ostomy care nursing management. Self‐efficacy ostomy care nursing management encompasses 24 items and three domains, which are clinical assessment, education and relationship, and teamwork. This research will have an impact on nursing education, as it addresses the need for a specific self‐efficacy assessment of ostomy care nursing management. Self‐efficacy ostomy care nursing management will have an impact on nurses and patients, as it can be used to improve nurses' self‐efficacy and clinical outcomes for patients in ostomy care. Abstract : 目的: 建立一种造口护理管理自我效能感量表, 并对其进行心理测量。 设计: 本研究采用多方法多阶段设计方法。 方法: 第一阶段的研究是由发展性任务组成的, 其中的项目是根据文学中涌现的主题生成的。随后, 专家小组对这些问题进行了讨论。第二阶段为量表的验证过程, 对量表的内容效度、构念效度、同时效度及内部一致性进行评估。验证过程在2018年1月至2019年1月期间进行。 结果: 造口护理自我效能感量表的最终版本包括24个项目, 分三个领域, 即临床评估领域、教育与关系领域、团队合作领域。量表包括面效度和内容效度、适当的构念和同时效度以及适当的内部一致性。 结论: 该量表可用于临床和教育研究。 影响: 本研究提出了第一个有效的和可靠的报告测量护士的自我效能在造口护理管理的发展和验证。自我效能造口护理管理包括 24个项目和3个领域, 即临床评估、教育和关系、团队合作。这项研究将对护理教育产生影响, 因为它能满足对造口护理管理进行特异性自我效能评估的需要。自我效能造口护理管理将对护士和患者产生影响, 因为它可以用来提高护士的自我效能和改善造口护理患者的临床结果。